Risk perceptions and changes in tobacco use in relation to Coronavirus Disease 2019 pandemic: A qualitative study on adolescent tobacco users in Hong Kong - Tianqi Chen; Lijun Wang; Yee Tak Derek Cheung; Man Ping Wang; Tai Hing Lam; Sai Yin Ho (Tobacco Induced Diseases)
Introduction Tobacco use is associated with an increased risk of Coronavirus Disease 2019 (COVID-19) infection, severe COVID-19 outcomes requiring intensive care, and mortality. We investigated the perceived risk of and changes in cigarette, e-cigarette (EC) and heated tobacco product (HTP) use in relation to COVID-19 in Hong Kong adolescent tobacco users.